EAACI guideline: Preventing the development of food allergy in infants and young children (2020 update). Issue 5 (29th March 2021) - Halken, Susanne; Muraro, Antonella; de Silva, Debra; Khaleva, Ekaterina; Angier, Elizabeth; Arasi, Stefania; Arshad, Hasan; Bahnson, Henry T.; Beyer, Kirsten; Boyle, Robert; du Toit, George; Ebisawa, Motohiro; et al.
Abstract: Background: This guideline from the European Academy of Allergy and Clinical Immunology (EAACI) recommends approaches to prevent the development of immediate‐onset / IgE‐mediated food allergy in infants and young children. It is an update of a 2014 EAACI guideline. Methods: The guideline was developed using the AGREE II framework and the GRADE approach. An international Task Force with representatives from 11 countries and different disciplinary and clinical backgrounds systematically reviewed research and considered expert opinion. Recommendations were created by weighing up benefits and harms, considering the certainty of evidence and examining values, preferences and resource implications. The guideline was peer‐reviewed by external experts, and feedback was incorporated from public consultation. Results: All of the recommendations about preventing food allergy relate to infants (up to 1 year) and young children (up to 5 years), regardless of risk of allergy. There was insufficient evidence about preventing food allergy in other age groups. The EAACI Task Force suggests avoiding the use of regular cow's milk formula as supplementary feed for breastfed infants in the first week of life. The EAACI Task Force suggests introducing well‐cooked, but not raw egg or uncooked pasteurized, egg into the infant diet as part of complementary feeding. In populations where there is a high prevalence of peanut allergy, the EAACI Task Force suggests introducing peanuts in an age‐appropriate form as part of complementary feeding. According to the studies, it appears that the most effective age to introduce egg and peanut is from four to 6 months of life. The EAACI Task Force suggests against the following for preventing food allergy: (i) avoiding dietary food allergens during pregnancy or breastfeeding; and (ii) using soy protein formula in the first 6 months of life as a means of preventing food allergy. There is no recommendation for or against the following: use of vitamin supplements, fish oil, prebiotics, probiotics or synbiotics in pregnancy, when breastfeeding or in infancy; altering the duration of exclusive breastfeeding; and hydrolysed infant formulas, regular cow's milk–based infant formula after a week of age or use of emollients. Conclusions: Key changes from the 2014 guideline include suggesting (i) the introduction of peanut and well‐cooked egg as part of complementary feeding (moderate certainty of evidence) and (ii) avoiding supplementation with regular cow's milk formula in the first week of life (low certainty of evidence). There remains uncertainty in how to prevent food allergy, and further well‐powered, multinational research using robust diagnostic criteria is needed. Abstract :